WORD CHOICE IN FORMAL AND INFORMAL ENGLISH: DIFFERENCES IN USAGE AND CONTEXT (Eureka Journal of Language, Culture & Social Change, 2026)
In this paper the differences between Formal and Informal English are discussed. Academic writing is often referred to as “formal”, but the teaching and assessment of formality can be challenging as formality has been conceptualised in many ways. A register variation is a variety of a language that is associated with extra-linguistic context. The relationship between a register and its context is functional: the linguistic features that make up a register are motivated by the needs and constraints of the communicative situation. Analysis shows that contrary to theorizing in variation sociolinguistics, probabilistic complexity differences between registers are not quantitatively simple: formal registers are consistently the most complex ones, while spoken registers are the least complex ones. 72 academic writing instructors were asked to rate the formality level of 60 short academic text experts on five-point scale. The excerpts were sampled from two publication types (university textbooks, journal articles) in three disciplines (psychology, biology, history). The results generally indicate that perceptions of formality can be explained by both linguistic features and situational characteristics.
Keywords: Formal English, informal English, academic writing, register variation, linguistic features, spoken registers, language variation, context, academic discourse, linguistic complexity, formality.